HbA1c AND THE RISK OF DIABETIC RETINOPATHY PROGRESSION: CURRENT EVIDENCE AND CLINICAL IMPLICATIONS - Julia Łukasik; Karolina Bałdys; Klaudia Jeziorowska; Maria Całusińska-Skowron; Aleksandra Regina Żmuda; Aleksandra Karolina Schmidt; Kornel Adrian Jarosz; Anna Kudłacik; Magdalena Franków; Oktawian Kaczmarek (International Journal of Innovative Technologies in Social Science, 2026)
Background: Diabetic retinopathy (DR) is one of the most common microvascular complications of diabetes mellitus and remains a leading cause of preventable vision loss worldwide. Glycated hemoglobin (HbA1c), reflecting long-term glycemic control, is widely recognized as an important biomarker for assessing the risk of diabetic complications. Objective: This narrative review aimed to summarize current evidence regarding the relationship between HbA1c levels and the development and progression of diabetic retinopathy, with particular emphasis on its clinical significance in risk assessment and disease prevention. Methods: A review of landmark randomized controlled trials, epidemiological studies, systematic reviews, meta-analyses, and current clinical guidelines was conducted. Evidence from the Diabetes Control and Complications Trial (DCCT), the United Kingdom Prospective Diabetes Study (UKPDS), the Wisconsin Epidemiologic Study of Diabetic Retinopathy (WESDR), ACCORD, ADVANCE, and recent reviews was synthesized to evaluate the role of HbA1c in diabetic retinopathy. Results: The available evidence consistently demonstrates that elevated HbA1c levels are strongly associated with an increased risk of developing and progressing diabetic retinopathy in both type 1 and type 2 diabetes mellitus. Sustained improvement in glycemic control significantly reduces the risk of retinal complications, although no universally accepted HbA1c threshold predicting disease onset has been established. HbA1c should therefore be interpreted as a continuous biomarker of retinal risk alongside other clinical risk factors. Conclusions: HbA1c remains one of the most valuable modifiable predictors of diabetic retinopathy and an essential component of individualized diabetes management. Optimizing long-term glycemic control, combined with regular ophthalmologic assessment and comprehensive risk factor management, remains the cornerstone of preventing diabetic retinopathy progression and preserving visual function.